Kropslig subjektivering - Cawood, Sarah Højgaard; Juelskjær, Malou (Kvinder, Køn & Forskning, 2005)
Hunting through poststructuralist feminist theories of the body, this article presents building blocks for a theory of bodily subjectification processes which works against generalising ideas and which prove useful for complex analytical investigations of how we become subjects in a bodily sense. The building blocks presented includes 1) Viewing the body as in a constant process of becoming). 2) Conceptualizing the body in intra-activity with other elements – bodily becoming is dependent upon other bodies and artefacts with which the body infolds. 3) Setting the body between sedimentation and change. These ideas are drawn from Judith Butler’s concept of performativity, Karen Barad’s theorization of materialization processes and Bruno Latour’s Actor Network Theory. The tools´ workings are demonstrated on an empirical example of bodily infoldings between 16 yearold Mette and a sexualized commercial.